Janus Nanoparticle Coupled Double‐Network Hydrogel. Issue 17 (15th May 2022) - Hou, Hanyi; Yang, Tiantian; Zhao, Yanran; Qi, Meiyuan; Song, Zhining; Xiao, Yi; Xu, Lai; Qu, Xiaozhong; Liang, Fuxin; Yang, Zhenzhong
Abstract: For double network (DN) hydrogels, their performance can be tuned by adjusting the interaction between their two networks. A novel DN hydrogel toughening approach is proposed by employing Janus nanoparticles (JNs) as crosslinkers to gain a conjoined‐network hydrogel. First, a kind of JNs modified by amino groups and quaternary ammonium salt is synthesized, named R3 N + ‐JN‐NH2 . The DN hydrogel is fabricated based on ionic coordination between calcium chloride (CaCl2 ) and sodium alginate (Alg), as well as covalent (benzoic imine) between glycol chitosan (GC) and benzaldehyde‐capped poly(ethylene oxide) (BzCHO−PEO−BzCHO). Based on the same covalent and ionic dynamic crosslinking mechanism, the added R3 N + ‐JN‐NH2 interacts with two networks to promote crosslinking to form a dually crosslinked structure. The R3 N + ‐JN‐NH2 effectively provides more energy dissipation, and the hydrogel with conjoined networks shows better compression resistance. Abstract : A new toughening method for DN hydrogel is developed. Janus nanoparticles with amino and quaternary ammonium salt functional groups are synthesized as crosslinkers to provide covalent and ionic dynamic bonds in DN hydrogel. The fracture energy and compressive modulus of the hydrogel are 0.071 MJ m −3 and 0.16 MPa respectively, with the particle content of 0.3 wt%.